Assessment of the professional dental cleaning knowledge, behavior and medical compliance among dentists, medical doctors and non-medical staffs: a cross sectional study in Chongqing, China - Qian Wang; Hengzhu Chen; Lin Jiang (BMC, 2022)
Abstract Background The professional dental cleaning (PDC) is an effective supplement that can make up for the lack of self-oral health care. Everyone should develop the habit of regular PDC. This study aimed to investigate the knowledge, behaviors and medical compliance of dentists, medical doctors and non-medical staffs about the PDC, identify the gaps, and provide information to help individuals develop healthy oral hygiene habit. Materials and methods A web-based survey with 21 questions designed based on the characteristics, the PDC knowledge, behaviors, and medical compliance of respondents. A cross-sectional study was conducted in the main districts of Chongqing, China, in the period of September-November 2020. A total of 456 respondents including 153 dentists, 137 medical doctors and 166 non-medical staffs in 3 communities and 4 hospitals were sampled online with multistage sampling and surveyed. The data was analyzed by chi-square test using IBM SPSS Statistics v. 21.0. Results The cognitive level and behavior of dentists on the PDC was significantly better than that of medical doctors and non-medical staffs (p = 0.000-0.044). The rates of not knowing "dental plaque" were 32.85% and 61.45%, of the medical doctors and non-medical staffs. Meanwhile, most of them had misunderstanding about effects of the PDC. They thought it would whiten teeth (72.99%, 80.72%), damage gums (16.79%, 19.88%) and teeth (15.33%, 21.69%), and create bigger gaps between teeth (24.82%, 33.13%). In terms of gum health and the PDC behavior, significant differences were observed, 23.53% of dentists experienced irritated gum bleeding in the last 12 months, 42.28% did not have their teeth cleaned professionally in the last 12 months, even 7.84% never had it before. Compared with it, in the same situation, the ratios of medical doctors and non-medical staffs were about 60% experiencing irritated gum bleeding, 69.34% and 77.71% not experiencing the PDC in the last 12 months, up to 33.58% and 45.18% never experienced it before. 41 respondents (8.99%) disagreed with the reasonable and necessary medical behaviors before the PDC. Conclusion People's understanding about the PDC was insufficient, and many people, included some dentists, had not developed the habit of regular dental cleaning. Our study provided a new understanding of the PDC among dentists, medical doctors, and non-medical staffs, which may help to improve their awareness and behavior of oral hygiene health, and establish the multidisciplinary collaborations between dentists and medical doctors.